Program Bimbingan Pranikah: Solusi Menghadapi Tantangan Pernikahan Modern - Iit Vicania; Najlatun Naqiyah; Budi Purwoko; Bakhrudin All Habsy (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Modern marriages are faced with complex challenges, such as changing social values, economic pressures, hampered communication, and mental unpreparedness. Premarital guidance is a strategic solution in preparing couples to live a harmonious and sustainable married life. This article aims to analyze literature related to premarital guidance programs, especially in responding to the challenges of modern marriage. Based on a literature review, an effective premarital guidance program includes a holistic approach that involves spiritual, emotional, financial, and communication aspects. Additionally, the integration of technology, such as online courses and interactive applications, has been shown to increase program accessibility and appeal. A religious values-based approach, especially in the context of the sakinah family, also makes a significant contribution to building a deeper understanding of the purpose of marriage. Recommendations for program development include adaptation to the socio-cultural context, use of interactive media, involvement of multidisciplinary professionals, and ongoing monitoring and evaluation. With a comprehensive approach, premarital guidance can be a strong foundation for overcoming the challenges of modern marriage while creating a harmonious and stable family.